CHARACTERISTICS OF DIGITAL DIDACTIC MATERIALS IN WORKING WITH PRESCHOOL CHILDREN - Levinets, Nataliia (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The article summarizes the experience of using digital didactic materials in the theory and practice of preschool education. The purpose of the study was to describe the types and detailed characteristics of digital didactic materials aimed at solving the tasks of harmonious education and personal development of the child. Following the purpose, the tasks were solved: to formulate the concept of “digital didactic materials,” carry out characteristics of digital didactic materials for preschool children, and to reveal the educational and developmental potential of digital didactic materials in working with preschool children.To achieve the purpose of the study, the methods of analysis, comparison and synthesis of psychological and pedagogical works, digital educational content presented in the public domain on the Internet, classification and systematization of theoretical provisions on the problems of digitalization of education, substantiation of the concept of “digital didactic materials” and development of specific characteristics of didactic materials that have educational and developmental potential in working with preschool children as in conditions preschool education institution, and in family.It is determined that an extensive array of information presented in the digital environment requires the development of proper support and clarification of the features of the content and methods of use in the educational process of a preschool education institution.According to the research results, there is a lack of a unified approach to interpreting the concept of “digital didactic materials”, different views on the specific characteristics of didactic materials, and disparity of opinions on the possibilities and necessity of using digital materials in working with preschool children.The analysis of the source base (research on the introduction of digital technologies in the educational process and various digital resources) allowed us to establish the opinion that combining the traditions of preschool didactics and the potential of the digital environment is a promising educational direction. In the context of temporary restriction of access to the real educational environment, digital resources allow for the provision of high-quality educational services, the continuity of educational influences, and the formation of skills of positive interaction with the resources of the digital environment.